Functional analysis and association studies of bovine MYOT gene with meat quality - ADOLIGBE, CAMUS; ZAN, L.; FAROUGOU, SOUAÏBOU (My University, 2016)
The main objective of the present work was to study the molecular mechanisms of MYOT gene expression and its association with beef production traits. MYOT gene is a multifunctional gene involved in muscle development, which makes it a candidate gene for the improvement of meat quantity and quality. In the current study, the full length of bovine MYOT gene cDNA spanning 2234 bp was successfully cloned using skeletal muscle tissue. Real-time PCR analysis revealed that the gene is highly expressed in skeletal muscle followed by heart and heart fat tissues. Bioinformatics analysis showed that bovine MYOT protein contain eight different conserved functional domains. Polymorphism analysis of the gene sequence showed correlation of its mutations with loin muscle area, backfat thickness and intramuscular fat (P < 0.05) in Chinese Qinchuan cattle breed. We have further investigated the longitudinal expression profile of the MYOT gene and its corresponding cell differentiation process during myotube formation. Expression of the gene was initiated on Day 3 of differentiation and scored a peak on Day 6. This is identical to the expression pattern exhibit by three other myotube markers included in this experiment (MYOG, MYL1 and MYF6). Hence, MYOT gene may play a pivotal role in myoblast fusion and could also be considered as myotube marker. As showed by Western blot analysis, protein expression of the gene started from Day 6 of differentiation and increased slightly with the increase in the number of days. Lentivirus-mediated down-regulation of MYOT has inhibited significantly the expression of type I (slow-oxidative) and type IIA (fast-oxidative) muscle fiber types. However the inhibition of the gene has led to the increase in expression of type IIX (fast glycolytic) muscle fiber. These suggest that MYOT gene could affect muscle fiber characteristics and subsequently sensory quality of cooked meat. In conclusion, our findings showed that MYOT gene is essential for the regulation of muscle traits, and its SNPs can be used as genetic markers to expedite genetic change using marker-assisted selection in cattle breeding.
Keywords: bovine; MYOT; gene; meat